KEBIJAKAN KRIMINALISASI TENTANG DEFORESTASI DI JAWA TIMUR - Moch. Choirul Rizal (Jurnal Hukum Samudra Keadilan, 2018)
Wahana Lingkungan Hidup Indonesia (Walhi) of East Java noted that 30% of forest in East Java is deforested every year due to land conversion, illegal logging, fire, and erosion. In fact, East Java has a legal policy in the form of local regulations that have a spirit against deforestation. However, the policy of such law substantially contains problematics, for example, the equation of formulation of criminal acts with the Law of the Republic of Indonesia Number 18 of 2013 on Prevention and Eradication of Forest Destruction, which resulted in the regional regulations will be ruled out. Therefore, this conceptual study offers an idea of ​​the need for an update to the criminalization policy on deforestation in the local regulation. In the future, the criminalization policy on deforestation in regional regulations in East Java should contain specific and unregulated formulations of criminal acts in the law, for example, prohibit any form of action that results in the capacity of communities to participate in the prevention and eradication of deforestation practices.